Aripiprazole-Associated Hypoprolactinemia in the Clinical Setting. Issue 4 (August 2016) - Sogawa, Rintaro; Shimomura, Yuki; Minami, Chikako; Maruo, Joji; Kunitake, Yutaka; Mizoguchi, Yoshito; Kawashima, Toshiro; Monji, Akira; Hara, Hideo
Abstract : Background: The increase in prolactin (PRL) levels is a common adverse effect that occurs when using conventional and atypical antipsychotic drugs. Aripiprazole (ARI) is beneficial for antipsychotic-associated hyperprolactinemia but has been reported to decrease PRL secretion. Therefore, we investigated blood levels of PRL in patients who had taken ARI alone or in combination with other antipsychotics. Methods: Retrospective information was obtained from 25 psychiatric patients who were prescribed ARI, and the blood levels of PRL were measured. Results: The incidence of hypoprolactinemia in the current study was 44.0% (11/25). Eighteen patients were treated with ARI alone and 7 received ARI in combination with other antipsychotics. The PRL value of patients who took ARI alone was significantly lower than those who were also taking other antipsychotics (5.45 ± 3.93 vs 10.85 ± 5.53, P = 0.02; mean ± SD). There was no significant correlation of the PRL levels and dose of ARI used in the 18 patients who had taken ARI alone. Limitations: This was a retrospective study, and the data were obtained from a small number of psychiatric patients treated with ARI. Conclusions: Monitoring of PRL levels in patients treated with ARI may be useful in minimizing hypoprolactinemia, which has the potential to negatively impact patients. In particular, hypoprolactinemia as a consequence of taking ARI should be discussed with patients of childbearing age and those with immune deficiencies.